The resistance of memories: Biographical accounts of the truncated lives of students and social service professionals who disappeared and were executed during the dictatorship in Chile (1973-1990).: Biographical accounts of the truncated lives of students and social service professionals who disappeared and were executed during the dictatorship in Chile (1973-1990). - Valenzuela Rebolledo, Paz (Critical Proposals in Social Work, 2022)
The book La Resistencia de las Memorias adds to a historiographic trend of Chilean social work in permanent development, as well as to the line of construction of memories about human rights and dictatorship in Chile, a field of political deepening that has been persistent from the academy, from civil society organizations, as well as various disciplines, including social work, fighting against the invisibilisation, denial and forgetting of crimes against humanity that occurred in Chile.